Accomplishment report for the community health nursing experience in partnership with Barangay Esperanza Ilaya, Alfonso, Cavite - Fuentes, Raya Kathreen T.; Paredes, Chris N. (Manila College of Nursing, University of the Philippines Manila, 2017)
According to records review, Barangay Esperanza Ilaya has a total population of 1568. With the comprehensive community diagnosis done by the first batch of student nurses, they were able to cover 1289 people which is comprised of 290 households. Through this survey, together with the data gathered from the PhilPEN screening, it was found out that half of the population of the residents, with ages 25 and above, are diagnosed and suspected to have hypertension. With this dat, the second batch of students analyzed the problem and have identified 3 main risk factors that may have been contributing to developing the said disease. These are having low fiber and high fat and salt diet, being active and passive smokers and having inadequate physical activity. To address these, the student nurses planned with the barangay in order to come up with health programs that would promote health and wellness. They have agreed to implement a mother class, zumba and sports fest and were a success. The implementation of the said programs did not end with the student nurses leaving the community. Beforehand, they have coordinated and set contract with chosen barangay residents to continue the programs. The goal was not only to finish the requirements but to develop sustainable programs that can lead the community towards lifestyle modifications and good health.
I. Introduction -- II. Objectives -- III. Methodology -- IV. Scope and limitations -- V. Community profile -- VI. PhilPEN update -- VII. Program development and implementation -- VIII. Process evaluation -- IX. Conclusion and recommendation -- X. Other health-related activities -- Bibliography -- Appendices
Includes bibliographies
Keywords: Intensive community experience